2020
DOI: 10.15407/zoo2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Molecular data confirm the species status of Neoechinorhynchus personatus and N. yamagutii (Acanthocephala, Neoechinorhynchidae) from the Atlantic and Pacific grey mullets (Teleostei, Mugilidae)

Abstract: Molecular Data Confi rm the Species Status of Neoechinorhynchus personatus and N. yamagutii (Acanthocephala, Neoechinorhynchidae) from the Atlantic and Pacifi c Grey Mullets (Teleostei, Mugilidae). Sarabeev, V., Tkach, Ie., Sueiro, R. A., Leiro, J. -Neoechinorhynchus is known to be the most diverse acanthocephalan taxon with worldwide distribution; its species are characterized by uniformity of anatomical organization. Th e taxonomic status of Neoechinorhynchus agilis s. l. from grey mullets was recently revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Van Cleave [36,37] suspected that N. agilis was restricted to the Mediterranean, but this is now known not to be. For example, species presumed to be N. agilis before the establishment of the species complex concept studies by Tkach et al [35], Sarabeev et al [31] and ours (this paper) were reported from M. cephalus in Taiwan [32], in the Indian Ocean near Tamil Nadu [17], and in Guyana [26], as well as in Japan, Scotland, and North America. Other observers including Linton [19][20][21], Van Cleave [36,37], Meyer [23], Yamaguti [40,41], Petrochenko [24], Gaevskaya et al [10], and Tepe and Oguz [34] reported N. agilis from at least 10 species of fish in the Black Sea and the Mediterranean, among other locations off the coasts of Scotland, North America, and Japan.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Van Cleave [36,37] suspected that N. agilis was restricted to the Mediterranean, but this is now known not to be. For example, species presumed to be N. agilis before the establishment of the species complex concept studies by Tkach et al [35], Sarabeev et al [31] and ours (this paper) were reported from M. cephalus in Taiwan [32], in the Indian Ocean near Tamil Nadu [17], and in Guyana [26], as well as in Japan, Scotland, and North America. Other observers including Linton [19][20][21], Van Cleave [36,37], Meyer [23], Yamaguti [40,41], Petrochenko [24], Gaevskaya et al [10], and Tepe and Oguz [34] reported N. agilis from at least 10 species of fish in the Black Sea and the Mediterranean, among other locations off the coasts of Scotland, North America, and Japan.…”
Section: Introductionmentioning
confidence: 83%
“…Tkach et al [35] and Sarabeev et al [31] (Table 2). In addition, the shorter lemnisci in N. ponticus occupy a considerably smaller trunk space distant from the anterior testis (Fig.…”
Section: Remarksmentioning
confidence: 95%
See 3 more Smart Citations